The Insulin/IGF System in Colorectal Cancer Development and Resistance to Therapy - Vigneri, Paolo Giovanni; Tirrò, Elena; Pennisi, Maria Stella; Massimino, Michele; Stella, Stefania; Romano, Chiara; Manzella, Livia (Frontiers in Oncology, 2015)
The Insulin/Insulin-like growth factor (IGF) system is a major determinant in the pathogenesis and progression of colorectal cancer (CRC). Indeed, several components of this signaling network including Insulin, IGF-1, IGF-2, the IGF-Binding Proteins, the Insulin Receptor (IR), the IGF-1 Receptor (IGF-1R) and Insulin Receptor Substrate Proteins 1-2 contribute to the transformation of normal colon epithelial cells. Moreover, the Insulin/IGF system is also implicated in the development of resistance to both chemotherapeutic drugs and Epidermal Growth Factor Receptor targeted agents. The identification of hybrid receptors comprising both the IR and IGF-1R adds further complexity to this signaling network. Thus, a comprehensive understanding of the biological functions performed by each component of the Insulin/IGF system is required to design successful drugs for the treatment of CRC patients.